ALMA Observations of Elias 2-24: A Protoplanetary Disk with Multiple Gaps in the Ophiuchus Molecular Cloud - Ferrero Sosa, Gabriel Antonio (2017)
We present ALMA 1.3 mm continuum observations at 0."2 (25 au) resolution of Elias 2-24, one of the largest andbrightest protoplanetary disks in the Ophiuchus Molecular Cloud, and we report the presence of three partiallyresolved concentric gaps located at ∼20, 52, and 87 au from the star. We perform radiative transfer modeling of thedisk to constrain its surface density and temperature radial profile and place the disk structure in the context ofmechanisms capable of forming narrow gaps such as condensation fronts and dynamical clearing by activelyforming planets. In particular, we estimate the disk temperature at the locations of the gaps to be 23, 15, and 12 K(at 20, 52, and 87 au, respectively), very close to the expected snowlines of CO (23-28 K) and N2 (12-15 K).Similarly, by assuming that the widths of the gaps correspond to 4-8x the Hill radii of forming planets (assuggested by numerical simulations), we estimate planet masses in the range of 0.2-1.5 MJup, 1.0-8.0 MJup, and 0.02-0.15 MJup for the inner, middle, and outer gap, respectively. Given the surface density profile of the disk, theamount of missing mass at the location of each one of these gaps (between 4 and 20 MJup) is more than sufficientto account for the formation of such planets.